The Cu regulon of the human fungal pathogen Cryptococcus neoformans H99: Cuf1 activates distinct genes in response to both Cu excess and deficiency - Ding, Chen (2011)
Cryptococcus neoformans is a human fungal pathogen that is the causative agent of cryptococcosis and fatal meningitis in immuno-compromised hosts. Recent studies suggest that copper (Cu) acquisition plays an important role in C. neoformans virulence, as mutants that lack Cuf1, which activates the Ctr4 high affinity Cu importer, are hypo-virulent in mouse models. To understand the constellation of Cu-responsive genes in C. neoformans and how their expression might contribute to virulence, we determined the transcript profile of C. neoformans in response to elevated Cu or Cu deficiency. We identified two metallothionein genes (CMT1 and CMT2), encoding cysteine-rich Cu binding and detoxifying proteins, whose expression is dramatically elevated in response to excess Cu. We identified a new C. neoformans Cu transporter, CnCtr1, that is induced by Cu deficiency and is distinct from CnCtr4 and which shows significant phylogenetic relationship to Ctr1 from other fungi. Surprisingly, in contrast to other fungal, we found that induction of CnCTR1 and CnCTR4 expression under Cu limitation, and CMT1 and CMT2 in response to Cu excess, are dependent on the CnCuf1 Cu metalloregulatory transcription factor. These studies set the stage for the evaluation of the specific Cuf1 target genes required for virulence in C. neoformans.